2018
DOI: 10.1055/s-0038-1675600
|View full text |Cite
|
Sign up to set email alerts
|

Proline 36 of the Factor XIII Activation Peptide Plays a Crucial Role in Substrate Recognition and Zymogen Activation

Abstract: The activation peptide of blood coagulation factor XIII (AP-FXIII) has important functions in stabilising the FXIII-A2 dimer and regulating FXIII activation. Contributions of many of its 37 amino acids to these functions have been described. However, the role of proline 36, which is adjacent to the thrombin cleavage site at Arg37, has not yet been studied in detail. We approached this question when we came across a patient with congenital FXIII deficiency in whom we detected a novel Pro36Ser mutation. We expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…This variant cannot be cleaved by thrombin, and crosslinking ability must be derived from FXIII-A° activated slowly by low physiological Ca 2+ levels. 47 These two variants reveal that both FXIII-A* and A° can be encountered in plasma. Further examples of wild-type FXIII-A° are found in cellular environments.…”
Section: Discussionmentioning
confidence: 96%
“…This variant cannot be cleaved by thrombin, and crosslinking ability must be derived from FXIII-A° activated slowly by low physiological Ca 2+ levels. 47 These two variants reveal that both FXIII-A* and A° can be encountered in plasma. Further examples of wild-type FXIII-A° are found in cellular environments.…”
Section: Discussionmentioning
confidence: 96%
“…However, several recent studies have shown that these heterozygous F13A gene variants can also have strong effects on FXIII function. 84,86 The Lys679Met heterozygous F13A variant in an autosomal dominant pattern was observed more frequently in…”
Section: Molecular Basis Of Heterozygous Fxiii Deficiencymentioning
confidence: 99%
“…Usually, antigen and activity are strongly correlated so that it may be enough to determine either antigen or activity levels. However, in cases of congenital FXIII type II deficiency, i.e., normal protein levels but reduced function, 11 and acquired FXIII deficiency due to inhibiting antibodies, 12,13 it is essential to measure both FXIII antigen and activity. A significantly reduced FXIII activity at normal FXIII antigen levels is also found in patients with afibrinogenemia, 14 again arguing for the determination of both FXIII activity and antigen.…”
Section: Difficulties In Fxiii Laboratory Assessmentmentioning
confidence: 99%